2004
DOI: 10.2741/1409
|View full text |Cite
|
Sign up to set email alerts
|

MMPS and TIMPS in ovarian physiology and pathophysiology

Abstract: The matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) have been postulated to play a critical role in the extracellular matrix (ECM) remodeling associated with follicular development. The gelatinases were localized to the theca of developing follicles and in the stroma of the rodent ovary. Gelatinolytic activity corresponded with the localization of MMP-2 and MMP-9 around the developing follicles and at the apex of preovulatory follicles. The TIMPs-1, -2, and -3 were localized to the stroma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 59 publications
(66 reference statements)
5
66
0
2
Order By: Relevance
“…In fact, it has been shown that their expression is significantly increased in inflammation (Shamamian et al, 2001) and in tumour invasiveness and metastatisation (Turck et al, 1996) processes. Metalloproteinases are in turn regulated by inhibitory molecules (Goldman and Shalev, 2004); the balance between the two molecular families being critical for control of proteolysis (Lu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that their expression is significantly increased in inflammation (Shamamian et al, 2001) and in tumour invasiveness and metastatisation (Turck et al, 1996) processes. Metalloproteinases are in turn regulated by inhibitory molecules (Goldman and Shalev, 2004); the balance between the two molecular families being critical for control of proteolysis (Lu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that MMPs and their inhibitors are important regulators in the tissue remodeling of the above-mentioned process (Hagglund et al 1999, Nothnick 2000, Simpson et al 2003, Goldman & Shalev 2004. Unlike its counterparts TIMP-1, -2, -3, the localization and temporal regulation of TIMP-4 in rodent ovary have so far not been investigated in detail (Curry & Wheeler 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, MMPs failure or reduced activity has been called into question for ECM derangements in subfertility and infertility, for aberrant follicle growth and deficiencies in ovulation ( Refs 29,31,32,33,34,35,36). Controlling ECM organisation, MMPs are actually involved in the bioavailability control of hormones, growth factors, and osmotically active molecules by regulating local accumulation and activation of these factors, as well as cell response to extracellular stimuli and cell to cell communications ( Refs 13,37,38,39,40,41).…”
Section: Protein Pathways Working In Human Follicular Fluid: the Futumentioning
confidence: 99%
“…In this respect, a down-regulation of TIMP-1 may have a detrimental effect in the ovulation and an altered MMPs/TIMPs ratio may lead to a precocious regression of the corpus luteum with consequent depletion in progesterone and estradiol synthesis, thus to reduce the negative feedback to LH pituitary secretion (Ref. 36).…”
Section: Protein Pathways Working In Human Follicular Fluid: the Futumentioning
confidence: 99%